Growth of breast muscles in European and Japanese quail raised in meat production system: a morphological analysis - CHRISTIAN D.N. FIGUEROA; FLAVIA K. CRUZ; ISABELLE N. KANEKO; RODRIGO A. BASAGLIA; CARLOS A.L. OLIVEIRA; FERNANDA L.A. ALMEIDA; TATIANA C. SANTOS (Anais da Academia Brasileira de Ciências, 2023)
Abstract Growth curves have been described in the quail but with no attention to the muscle composing of the breast. The description of the characteristics of growth curves to body weight and to breast muscle was the aim of this study. Morphological development of Musculus supracoracoideus and Musculus pectoralis in European and Japanese quail was assessed from the final incubation of to 35 days. Gompertz models were adjusted with maximum growth rates to body weight, breast weight, and Musculus pectoralis and supracoracoideus weight at 17.6; 22.2; 23.5, and 21.4 days. The European quail had a higher body and breast weight at maturity. Musculus supracoracoideus developed faster in both subspecies but with larger Musculus pectoralis. Both musculus had a greater number of fibers type IIA and largest fibers IIB, with quadratically increasing in fiber diameter with age in both subspecies and muscles. At 35 days, results of meat quality indicated similarity between genders and subspecies, with darker and redness breast meat in Japanese quail. In conclusion, breast weight gain was a result of type IIA and IIB fiber hypertrophy in both muscles and, despite the difference in size and aptitude, Japanese and European quail showed similar body and muscle growth patterns.